IMPROVING STUDENTS’ READING COMPREHENSION IN LEARNING ENGLISH NARRATIVE TEXT THROUGH SKIMMING TECHNIQUE - Al Juska Sasni Akbar; Dinar Romadina (JELLi Journal, 2022)
This study focused on the effect of the use of Skimming Techniques on the Reading Comprehension of eleventh grade students of TKJ SMK Pelita Ciampea. The purpose of this study is to determine the effect of the use of Skimming Techniques on the Reading Comprehension of Eleventh grade TKJ SMK Pelita Ciampea. This research used quantitative research using Pre-test and Post-test. The writer used normality test, homogeneity test, and T-test. The result of the post-test showed that the experimental class after giving treatment had significouldt effect. To measure t-test result the writer used formula for a 0,05% with df 25+25 - 2 = 48, it was gained ttable with a = 0,05 = 1,67793 and tcount = 13,483. Thus, tcount > t table (13,483 > 1,67793). From the result of t-test the writer concluded that H0 was rejected and Ha was accepted. Based on the result Improving Students’ Reading Comprehension In Learning English Narrative Text Through Skimming Technique is very significouldt. It is proven that Narrative Text through Skimming Technique was effective in students' reading comprehension